Studi Keanekaragaman Kupu-kupu (Papilionoidea) Berdasarkan Ketinggian di Kawasan Gunung Galunggung Kabupaten Tasikmalaya - Ilham Pahman; Diana Hernawati; Diki Muhamad Chaidir (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Papilionoidea or better known as butterflies is a type of insect that is often found around us. This study aims to analyze the diversity of butterflies in the Mount Galunggung Region, Tasikmalaya Regency based on different heights. The method used in this research is descriptive quantitative with the VES (Visual Encounter Surveys) technique for 6 days within 4 weeks, 09.00-11.00 WIB and 13.00-15.00 WIB at 3 observation stations, including: Cimedang waterfall area (700 masl ), Gado Bangkong waterfall area (800 masl), and Cikahuripan waterfall area (950 masl). The calculated observational data includes: Shannon-Wiener diversity index (H'), species evenness index (E), species richness index (R), dominance index (D), and similarity index (IS), as well as environmental parameter measurements including: height , temperature, light intensity, humidity, and wind speed. The results of the observations showed that there were 1,071 individual butterflies from 41 species that were successfully found. The Nymphalidae family is the most common butterfly with 22 species, and the most common butterfly species are Jamies celeno, Ypthima pandocus, and Lampides boeticus. Overall, the diversity value of the Galunggung Mountain Area as a whole is 3.10 which is classified as a high category, an evenness index of 0.84 is classified as a stable category, a species richness index of 5.73 is classified as a high category, and a dominance index of 0.06 is classified as a low category.